Quality of wheat (Triticum aestivum) and nutrient status in soil as influenced by organic and inorganic sources of nutrients - SINGH, RAVINDRA; AGARWAL, S K; JAT, M L (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during the winter season of 1997-97 and 1997-98 on sandy-loam soil of Hisar, Haryana, to study the effect of organic and inorganic sources of nitrogen on quality of wheat (Triticum aestivum L. emend. Fiori & Paol.) and nutrient balance in soil. The protein content in grain improved significantly by 1.48% with farmyard manure @ 10 tonnes/ha during 1996-97 and by 2.59% with 20 tonnes/ha during 1997-98 respectively. Sedimentation value of grain was not affected by farmyard manure during both the years. Application of farmyard manure @ 10 tonnes/ha significantly enhanced the N (2.48%), P (6.66 and 6.89) and K (4.76 and 5.12%) .content in grain and their total uptake (22.63,29.47 and 15.95,28.31,17.76%) by wheat crop over control during both the years except N content in grain during 1996-97. Maximum protein content of 11.12 and 11.30% with 180 kg N/ha and sedimentation value (37.73 and 34.58 ml) of wheat grain was recorded with balance application of fertilizer during 1996-97 and 1997-98 respectively. The increase in fertility levels up to recommended N P ZnSO 4 enhanced the N, P and K content and their uptake in grain and straw of wheat during both the years. A positive nutrient balance of N (93.7 and 214.3 kg/ha), P (16.8 and 39.2 kg/ha) and K (71.1 and 183.7 kg/ha) was observed at higher levels of farmyard manure (20 and 30 tonnes/ha) application, whereas it was negative at the control and sale application of nitrogen fertilizer.